2012
DOI: 10.1002/ajmg.a.35624
|View full text |Cite
|
Sign up to set email alerts
|

Death rates in the U.S. due to Krabbe disease and related leukodystrophy and lysosomal storage diseases

Abstract: Leukodystrophies (LD) and lysosomal storage disorders (LSD) have generated increased interest recently as targets for newborn screening programs. Accurate epidemiological benchmarks are needed in the U.S. Age-specific mortality rates were estimated for Krabbe disease (KD) and nine related disorders. U.S. mortality records with E75.2 cause of death code during 1999-2004 were collected from 11 open record states. All E75.2 deaths in the United States were distributed into specific disease type based on proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 18 publications
1
49
0
Order By: Relevance
“…Age-specific mortality rates have been published for the United States, 38 but have not been published for any other country. Although not treated at length in the current paper, mortality rates provide useful information and should be similarly estimated and published for countries outside of the United States.…”
Section: Discussion and Recommendations For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Age-specific mortality rates have been published for the United States, 38 but have not been published for any other country. Although not treated at length in the current paper, mortality rates provide useful information and should be similarly estimated and published for countries outside of the United States.…”
Section: Discussion and Recommendations For Future Researchmentioning
confidence: 99%
“…It was found that mortality in children less than five years of age (0.994 deaths per year per million children) was greater than mortality in older individuals (0.007 deaths per year per million individuals). Barczykowski et al 38 also showed that the yearly mortality rate in children less than 5 y of age due to Krabbe disease is a good approximation to the incidence rate of the early infantile form of Krabbe disease.…”
Section: What Parameters Are Estimated?mentioning
confidence: 99%
See 1 more Smart Citation
“…GLD is an orphan disease, and it is often grouped together with other infrequent diseases of CNS white matter referred to as leukodystrophies . In the general population, GLD has a prevalence of 1:250,000 among live births (Barczykowski et al, ). This infantile form of the disease is fatal, with death before the age of 2 years.…”
Section: Brief Overview Of Gldmentioning
confidence: 99%
“…However, a recent study using death rates estimates the birth prevalence at about 1-250,000. 24 The birth rate for Krabbe disease is higher among certain ethnic groups. As the birth demographics change in the United States population, the incidence of Krabbe disease may change.…”
Section: Clinical Featuresmentioning
confidence: 99%